A new phenotype of aldolase a deficiency in a 14 year-old boy with epilepsy and rhabdomyolysis - case report - Lucia Santoro; Dorina Pjetraj; Virtut Velmishi; Carmen Campana; Carlo Catassi; Carlo Dionisi-Vici; Arianna Maiorana (BMC, 2022)
Abstract Background Glycogen storage disease type XII is a rare metabolic disease resulting from Aldolase A deficiency that causes muscle glycogen accumulation, with crisis of rhabdomyolysis and hemolytic anemia. In the very few cases described, rhabdomyolysis crises are caused by fever and/or exercise and can accompany acute hemolytic anemia. Although currently there is no therapy available for this disease, the guidelines for the management of other forms of glycogen storage diseases recommend a nutritional therapy in order to avoid hypoglycemia or prevent exercise-induced rhabdomyolysis. Case presentation In this case report we describe a new phenotype of the disease in a 14-year-old boy, characterized by seizures and rhabdomyolysis. Beside an antiepileptic treatment, we propose a new therapeutic approach based on ketogenic diet in order to supply an energetic substrate for skeletal muscle and neurons. Conclusions The anti-epileptic therapy and the dietetic approach were well tolerated by the patient who showed good compliance. This led to a deceleration of the disease with no other acute episodes of seizures and rhabdomyolysis, without any side effects observed.